(untitled) - Sunarsih, Mohammad Saleh , Syamsul Huda , Wayan Subagiarta (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The research aims to determine the effect of minimum wages on employment and welfare of the people in the ex-Residency of Besuki, east java, Indonesia. Related to this, whether the increase in wages is consistent with an increase in labor absorption and the welfare of the people who are pockets of poverty in the ex- Residency of Besuki, east java province, Indonesia. Research using eviews 9.0 analysis tools. Data collection methods from the east java central statistics agency (BPS) in 2005 - 2017 related to the district minimum wage, employment, and community welfare through the human development index (HDI). The analysis concluded that the district minimum wage had a positive and significant effect on the employment and welfare of the community. The findings of this study conclude that minimum wages only apply to several commercial sectors and are not extended to the public (non-profit) sector. The high number of employment is because they receive wages below the minimum wage standard because there is no other choice with consideration than being unemployed means that they do not get any wages at all and cannot meet basic needs.